Determinants of Rice Consumption in South Sulawesi With A Panel Data Approach - Abdul Rahman (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the factors that affect rice consumption in South Sulawesi Province using a panel data approach for 2018–2024. The dependent variables used are rice consumption (tons), while the independent variables include per capita income, household size, rice production, human development index (HDI), and percentage of poor population. The analysis was performed with a panel data regression model using R software, with a series of model specification tests including the Chow test, the Hausman test, and the Lagrange Multiplier (LM) test. The best model obtained is the Fixed Effect Model (FEM). Partially, the variables of household size and rice production had a significant negative effect on rice consumption, while HDI had a significant positive effect. The variables of per capita income and poverty level have a negative but not significant effect. These results indicate that rice consumption in South Sulawesi is more influenced by social aspects and quality of life than purely economic factors. These findings affirm the importance of food security policies that focus on improving human development, rice distribution efficiency, and strengthening social protection programs to maintain the stability of household food consumption.